Influence of interpersonal communication of chairman and employees on employee performance Inna Parapat Hotel and Resort - Fazhari, Syafrisya; Rudianto, Rudianto (Universitas Ahmad Dahlan, 2022)
This research is motivated by the rapid growth of technology and the increasingly dynamic patterns of human communication both as personal and interpersonal. This study aims to determine the influence of interpersonal communication between leaders and employees on employee performance at Inna Parapat Hotel and Resort. The theory used in this research is De Vito's theory which emphasizes interpersonal communication patterns while the employee performance approach uses the Robbins theory. The research method used is quantitative. This type of research uses associative research or research to determine the relationship between two variables. The study population was 93 people and 48 people were sampled using simple random sampling as the sampling technique. The data obtained is the result of a questionnaire whose answers are accumulated and described in narrative form. The conclusion from the research conducted is the influence of interpersonal communication on employee performance at the Inna Parapat Hotel and Resort.Â